Faktor Risiko Aktivitas Fisik, Indeks Massa Tubuh, Usia Sel, Dan Pekerjaan Terhadap Tingkat Stress - Berbudi B L, Abdurahman; Achwan, Achwan; Pambudi, Restu Arya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Introduction: A person's activities and a very dense environment in a big city which makes stress become higher than someone who lives in a rural area, one's work activities in urban areas tend to be more dense and unhealthy eating patterns are more common in urban people who tend to look for fast food where this affects the body mass index, cell age and stress level of a person, low physical activity and also increasing age in a person who lives in a big city can also affect a person's stress level. The purpose of this study was to determine the risk factors associated with stress such as physical activity, body mass index, age, cell age, and occupation. Design of this study is discovery where the research was carried out from a public health service clinic in pamulang. The number of samples in this study were 130 people, each patient who came was given a questionnaire and measured the age of the cells. The results of this study analysis by chi square, it was found that physical activity with stress got pearson r value 0.154 p 0.092, bmi with stress r 0.096 p 0.03, age of cells with stress r 0.76 p 0.012, occupation with stress r 0.103, p 0.083, can dis that the risk factors for physical activity with stress, and occupation with stress have no significant relationship p> 0.05, bmi with stress, cell age with stress has a significant relationship p <0.05. Keywords: Physical Activity, BMI, age cell, Occupation, and stress